Protection conferred by commercial NDV live attenuated and double recombinant HVT vaccines against virulent California 2018 Newcastle disease virus (NDV) in chickens. Issue 34 (22nd July 2020) - Ferreira, Helena L.; Reilley, Alexandra M.; Goldenberg, Dana; Ortiz, Ivan R.A.; Gallardo, Rodrigo A.; Suarez, David L.
Abstract: Vaccines against virulent Newcastle disease virus (NDV) are widely available and can be protective, but improved vaccination protocols are needed to prevent clinical disease and reduce virus circulation. The present study evaluated the efficacy of two commercial vaccines alone or in combination: a live attenuated NDV vaccine (LV) and a recombinant herpesvirus of turkeys vector expressing the fusion protein of NDV and the virus protein 2 of infectious bursal disease virus (rHVT-ND-IBD). Chickens were vaccinated with one of four vaccination protocols: live vaccine (LV) at 1 and 11 days of age (DOA), rHVT ND-IBD and LV at 1 DOA, rHVT ND-IBD at 1 DOA boosted with an LV at 11 DOA, and rHVT ND-IBD at 1 DOA. The vaccinated birds were challenged at different time points (3 or 4 weeks of age) with the California 2018 virus. The mortality, clinical signs, mean death time (MDT), humoral response before and after vaccination, and virus shedding after challenge were evaluated. All vaccination protocols were able to prevent mortality, reduce virus shedding, and induce antibody levels before the challenge at 3 and 4 weeks-old. Overall, the antibody levels before the challenge at 4 weeks were significantly higher in all groups vaccinated with the rHVT ND-IBD when compared to levels in 3 week old birds. The combination of recombinant rHVT ND-IBD with a live vaccine at one-day-old seems to be a better combination, due to the absence of clinical signs, higher antibody levels pre and post-challenge, and reduced virus shedding at any time point after the challenge at 3 or 4 weeks of age with the California 2018 virus.